The econnomy and the knowledge society. Towards the third revolution: information - Acevedo Borrego, Adolfo (2009)
Knowledge is a body of data and information for a specific purpose may be the unveiling of the truth or solving a problem. Within the Baconian perspective, the economy is human activity that uses scarce resources to generate and distribute wealth. Development is a process of economic growth and greater social welfare. The current process is characterized by technological innovation, global trade of goods and services, and management and exchange of basic and applied knowledge among academic and business communities. This phenomenon is called the Information and Knowledge Society (IKS) that comes with boom of convergence of high technology sectors and structure of global information networks that enables the consolidation of productive chains, raising competitiveness with global impact.